Eficacia de la ivermectina y del albendazol sulfóxido para el control de nematodos gastrointestinales en ovejas Pelibuey - Collazo-Preciado, Getsemany (2023)
A study was conducted to evaluate the efficacy of ivermectin and albendazole sulfoxide for the control of gastrointestinal nematodes. Thirty Pelibuey ewes were randomly assigned to three experimental groups: Ivermectin 4% (10.2 mg/kg), albendazole sulfoxide 17% (3.75 mg/kg) and an untreated control group. Faecal samples were collected before drug administration (day 0) and on days 7, 14, 21, 28, 35, and 42 post-treatment. The quantitative diagnosis of the eggs was carried out using the McMaster technique and cultures were carried out to recover larvae by the migration method with the Baermann apparatus. The anthelmintic efficacy of the treatments was determined by the Abbott's formula and the effect of anthelmintics on the number of eggs per gram of faeces (EPG) by an analysis of variance with a completely randomized design. The most abundant species were Haemonchus contortus and Strongyloides papillosus. A significant decrease in the amount of EPG was observed from day 7 of treatment with both anthelmintics, with albendazole sulfoxide and ivermectin showing efficacy above 95% from day 7 and 14 post-treatment, respectively, until day 21. At 24 h post-treatment, ivermectin showed lower efficacy than albendazole sulfoxide (69.5 vs 90.9% respectively), but efficacy was similar and above 90% for both drugs from day 7. The efficacy of lbendazole sulfoxide against Haemonchus contortus larvae was 88.2% at 24 h post-treatment compared to 69.5% for ivermectin, but only the latter showed an efficacy greater than 95% on days 14 and 21 post-administration. It is concluded that albendazole sulfoxide has a faster effect and a longer efficacy for the control of gastrointestinal nematode eggs, while ivermectin showed greater efficacy for the control of Haemonchus contortus larvae without evidence of resistance to both drugs.